BIOINSECTICIDAL ACTIVITY EVALUATION OF PERGULARIA TOMENTOSA AND URTICA DIOICA AGAINST INSECT VECTORS? MOSQUITOES AND PHLEBOTOMINE SAND FLIES - Gaouaoui Randa, Zeroual Samir, Lillia Lembrouk, Boudjelida Hamid (Chelonian Research Foundation, 2024)
ABSTRACT Plant extracts are showing to be a good alternative sources, instead of conventional pesticides, for pest and vector insect control agents. Plant extracts and essential oils were used as bioinsecticides products and are exhibited a toxicity to insect pests with a low effects on non target animals and environment. Pergularia tomentosa and Urtica dioica are plants that have been widely used in traditional medicine since ancient times due to their different medicinal properties. The purpose of the present study was to assess the adulticidal activities of a medicinal plant, P. tomentosa and U. dioica , against the most abundant insect vectors in Algeria; the domestic mosquito Culex pipiens and phlebotomine sand flie Phlebotomus papatasi, under laboratory conditions. The toxicological assays were carried out using a ethanolic extracts formulation of P. tomentosa and U. dioica separately, with different concentrations (150, 200, 300, 400 µl/ml air) on the adults of the mosquito and phlebotomine sand flies. The obtained results showed a highly significant toxic effect of these extract plants for the tested concentrations, with concentration response relation-ship mortality, for the treated adults of both insect species. The lethal concentrations values with confidence limits (LC50 and LC90) against mosquito, were estimated at 179.9, 266 µl/ml P. tomentosa and at 216.5 and 383.8 µl/ml for U. dioica . Whereas the LC50 and LC90 values of the bioassay against phlebotomine sand flies were higher, with 192.7 and 278 µl/ml for P. tomentosa and 184, 315 µl/ml U. dioica . It was concluded that P. tomentosa and U. dioica extracts exhibit an insecticidal effects against adult mosquito and phlebotomine sand flies and could be considered as a potential alternative to the widely used the conventional insecticides.